2021
DOI: 10.22616/j.landarchart.2020.17.03
|View full text |Cite
|
Sign up to set email alerts
|

The model of trees for the restoration of historical manor parks in Estonia

Abstract: The aim of this article is to work out the methodological basis for the restoration of historical manor parks according to the requirements of the Florence Charter. This is why the park is not studied as an object of biodiversity but as a built monument and an architectural piece, whose composition is mainly created by woody plants particularly trees. The purpose of the current research was to clarify the proportion of examples of distinct tree species in manor parks today and to determine the main tree and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In order to develop the value assessment (value implies certain phenomena or objects that have material (economic), social, or cultural significance [16]) of man-made protected parks, the following methods were applied: classification of protected nature values [17], methodology for determining the dendrological value and level of preservation of landscape objects [18], assessment of unique trees [19], in accordance with the Florentine Charter, components of the architectural composition of historical parks: plan and relief; types of plantings, plant species, structural and decorative features; water elements [4], approaches to applying the design of landscape groups of plants and their medicinal properties [20], classification of ecosystem services [21], assessment of ecosystem services [21][22][23]. The study evaluated each value in points depending on the number of features found in parks (PMLA and CNM), and then, according to the classification of ecosystem services and classified them into four groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to develop the value assessment (value implies certain phenomena or objects that have material (economic), social, or cultural significance [16]) of man-made protected parks, the following methods were applied: classification of protected nature values [17], methodology for determining the dendrological value and level of preservation of landscape objects [18], assessment of unique trees [19], in accordance with the Florentine Charter, components of the architectural composition of historical parks: plan and relief; types of plantings, plant species, structural and decorative features; water elements [4], approaches to applying the design of landscape groups of plants and their medicinal properties [20], classification of ecosystem services [21], assessment of ecosystem services [21][22][23]. The study evaluated each value in points depending on the number of features found in parks (PMLA and CNM), and then, according to the classification of ecosystem services and classified them into four groups.…”
Section: Methodsmentioning
confidence: 99%
“…A historical garden according to the Florence Charter [3] is an architectural and park composition (the components are mainly plants that are in constant dynamics), which is of interest to the public from a historical or artistic standpoint. Parks can be considered not only as an object of biodiversity, but also as manmade architectural objects that use woody plants in the composition [4]. Countries that have well-established park and gardening traditions, such as the United Kingdom, the United States, France, etc., pay considerable attention to the preservation, restoration, and management of historical gardens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation